EVALUACIÓN DE NANOPARTÍCULAS DE SÍLICE EN LA PRODUCCIÓN DE PIMIENTO (Capsicum annumm L.) - Llerena Fuentes, Bryan Lincoln (2023)
The application of silica nanoparticles increases plant photosynthesis, facilitating the transport of nutrients through the xylem. The objective of this research was to evaluate the effect of silica nanoparticles on pepper production. The research was carried out in the greenhouse of the Campus Experimental “La María”, in Mocache, Los Ríos province, Ecuador. In a completely randomized design, three doses of silica nanoparticles at 0.5, 7, 9 ppm were evaluated, plus a control without application, for a total of four treatments, with four repetitions, each consisting of 10 plants, for a total 40 plants per treatment.